2019
DOI: 10.1186/s12958-019-0457-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat diet impairs follicular development of offspring through intraovarian kisspeptin/GPR54 system

Abstract: BackgroundExcessive gestational weight gain (GWG), which is associated with adverse long-term effects on the health of the offspring, has become a major clinical problem. Accumulating evidence indicates that the ovary kisspeptin/GPR54 system directly participates in a series of physiological activities. We used a model of high-fat diet (HFD) during gestational to investigate offspring’s ovarian function and whether kisspeptin/GPR54 system is involved.MethodsAfter introducing the male and confirmation of mating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…Although we know that the KD exhibits anti-inflammatory properties 16 , our experiments demonstrate the adverse effects of the maternal KD on the follicular count of offspring. These adverse effects in our study were similar to the findings found due to studies using HFDs 17 . KD, which is similar to HFD in content, affects ovaries similar to HFD.…”
Section: Discussionsupporting
confidence: 92%
“…Although we know that the KD exhibits anti-inflammatory properties 16 , our experiments demonstrate the adverse effects of the maternal KD on the follicular count of offspring. These adverse effects in our study were similar to the findings found due to studies using HFDs 17 . KD, which is similar to HFD in content, affects ovaries similar to HFD.…”
Section: Discussionsupporting
confidence: 92%
“…Treatment of FFA-loaded hepatocytes substantially decreased TG accumulation ( Figure 10B ). These KP concentrations were selected based on their ability to stimulate insulin secretion from isolated human pancreatic islets ( 58 ) and to activate KISS1R in vitro and in vivo ( 59 62 ). In contrast, KP failed to suppress TG levels in hepatocytes isolated from LKO mice ( Figure 10C ).…”
Section: Resultsmentioning
confidence: 99%
“…In mammals, E 2 secretion rises in the late follicular phase during puberty in females [ 59 ]. The function and structure of the ovary gradually improve during puberty, and the content of E 2 and P 4 in the blood increases during the first ovulation and maintains the subsequent estrous cycle [ 60 ]. The more the primary and secondary follicles in the ovary may increase E 2 secretion.…”
Section: Discussionmentioning
confidence: 99%